(untitled) (Research, Society and Development, 2021)
Chronic patients who have undergone a surgical procedure are in a period of fragility. In view of this, the nurse in Primary Health Care has an important role in the care process, as he needs to have skills to fortify the patient, helping him to face difficulties related to his disease, promoting his security and self-confidence. Being of this professional’s particularity, the patient’s different look, analyzing him as a biopsychosocial being. Based on this reality, the objective of this study is to highlight the scientific production about the nursing care process for post-surgical cardiac patients in Primary Health Care. This is an Integrative Literature Review, which seeks to deepen about the topic of interest, through analysis and synthesis of primary studies. The development of this study took place in five stages: formulation of the problem, literature search, data evaluation, data analysis and presentation. Regarding the results, it was found that patients affected by cardiovascular disea-ses and submitted to cardiac surgery, are subject to face several changes in their lives, involving physical, emotional and psychosocial aspects. Finally, it was noticed that through relevant assistance techniques, such as therapeutic listening, and through the nurse’s different view, understanding the patient as a broad and complex being, nursing care in Primary Health Care is presented differently, resulting in a positive application to the care process of this group of patients.